URGENSI FULL DAY SCHOOL DALAM MENINGKATKAN KOMPETENSI SIKAP SPIRITUAL DAN SOSIAL SISWA DI SMP UNGGULAN NU MOJOAGUNG JOMBANG - Masfufah, Idatul; Anshori, Solihul (Al Tadib : Jurnal Ilmu Pendidikan, 2019)
Abstract: This article discusses the urgency of full day school in improvingspiritual competence and social students in SMP Unggulan NU MojoagungJombang. Using a qualitative approach with interviews, observation, anddocumentation as a data collection technique, the author uses the Miles andHubberman models, data reduction, data viewing, and verification / conclusiondrawing. The results of the study (1) the competency of the spiritual and socialattitudes of SMP Unggulan NU Mojoagung Jombang. School students showed anincrease with the implementation of full day school education. Spiritual attitudesrelated to faith and piety, and morality, independence, democracy, andresponsibility to become accustomed. Also a sense of responsibility in fulfillingthe obligations of religion. Students carry out worship without being ordered.Students act politely when interacting with the community around theirenvironment, even though everything is inseparable from the support of parentsbut the habituation done at school is very positive. Keywords: Social and spiritual competence, habituation